2021
DOI: 10.1186/s12903-021-01461-y
|View full text |Cite|
|
Sign up to set email alerts
|

Maxillary and mandibular dental arch forms in a Jordanian population with normal occlusion

Abstract: Background Ethnic background has been claimed to affect arch form. The purpose of this study was to describe and elucidate the maxillary and mandibular arch forms in Jordanian population and to develop a classification method for these forms which could be employed to construct orthodontic archwires accordingly. Methods The sample was comprised of study casts of five hundred and twenty subjects (231 males and 289 females with a mean age of 15.4 ± 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The ovoid arch form was the dominant arch form in the current study which is in agreement with Saeed and Mageet [ 38 ] in the Sudanese population. In the same direction, Aljayousi et al found similar results in the Jordanian population, but their second dominant arch form was the tapered (36.2%), followed by the square arch form (16.8%) [ 39 ].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The ovoid arch form was the dominant arch form in the current study which is in agreement with Saeed and Mageet [ 38 ] in the Sudanese population. In the same direction, Aljayousi et al found similar results in the Jordanian population, but their second dominant arch form was the tapered (36.2%), followed by the square arch form (16.8%) [ 39 ].…”
Section: Discussionmentioning
confidence: 77%
“…However, considering using a different procedure for arch form evaluation that takes in the account evaluation of the position of all teeth might be more sensitive to give the exact dental arch form, whether by using a spherical system. whether by using a spherical (polar) coordinate system[ 41 ] or by utilizing computer software to obtain the “polynomial function” that best describes the curve corresponding to the dental arch form [ 39 ] could give us more detailed information regarding the expected bone thickness for each arch form. Further study that addresses these limitations is required to clarify these points and to distinguish and confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the arch form, it was found that anterior arch length together with intercanine width (ICW) play an important role in determining the arch form, as these measurements shape the anterior part of the arch, thus affect the form of the arch (Bayome et al 2011;Aljayousi et al 2021).…”
Section: Discussionmentioning
confidence: 99%